SOCRATIC METHODS IN EDUCATION BASED ON CONFLICT DIALOGUE - Akhmedov B.A. (Sciental Journals Publishing, 2024)
The structure and plot of the Socratic dialogue are analyzed. The main forms and principles of the method are revealed, and its results are correlated with the requirements of the Republican basic general education for the possible approbation of the method by teachers of humanities.
Keywords: Humanities; Pedagogy; Pedagogical Methods; Socratic Dialogue